Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

Asymmetric transfer hydrogenation of imines in water by varying the ratio of formic acid to triethylamine - Shende, Vaishali S.; Deshpande, Sudhindra H.; Shingote, Savita K.; Joseph, Anu; Kelkar, Ashutosh A. (Organic Letters, 2015)
Asymmetric transfer hydrogenation (ATH) of imines has been performed with variation in formic acid (F) and triethylamine (T) molar ratios in water. The F/T ratio is shown to affect both the reduction rate and enantioselectivity, with the optimum ratio being 1.1 in the ATH of imines with the Rh-(1S,2S)-TsDPEN catalyst. Use of methanol as a cosolvent enhanced reduction activity. A variety of imine substrates have been reduced, affording high yields (94-98%) and good to excellent enantioselectivities (89-98%). In comparison with the common azeotropic F-T system, the reduction with 1.1/1 F/T is faster.

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Asymmetric transfer hydrogenation of cyclic imines in water with a versatile hydrogen donorformic acid/N-methylpiperidine: rapid access to highly enantioselective amines - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kelkar, Ashutosh. A. (Chemistryselect, 2016)
Asymmetric transfer hydrogenation (ATH) of cyclic imines in water has been investigated for the first time by using HCOOH in combination with bases other than triethylamine as H donor. Effect of FA/Base ratio has shown significant impact on activity and enantioselectivity for ATH reaction in water. Use of methanol as a co-solvent improved the reduction performance. FA/N-methylpiperidine was found to be excellent, versatile hydrogen donor for ATH of imine 6,7-dimethoxy-1-methyl-3,4-dihy-droisoquinoline (1a) giving by far the highest noted TOF value of 5940 h(-1). ATH of-different imines derivatives including 3, 4-dihydoisoquinolines, beta-carbolines and cyclic sulfonyl imines have been performed with excellent activity (91-99% yield) and enantioselectivity (88-97%) in very short time (1-2 min). This is very simple protocol for rapid access to enantioselective amines with very new and versatile hydrogen donor 1.1 FA/Nmethylpiperidine.

Graphene oxide-cyclopentylamine (GO-d-CP) liquid crystals as a novel alignment medium for anisotropic nmr with analyte recovery - Jatheendranath, Sandesh Chickmagalur; Das, Akhi; Deshpande, Sudhindra H.; Nath, Nilamoni; Maier, Walter; Streitferdt, Verena; Marelli, Udaya Kiran (Chemistry—Methods, 2025)
In this study, we present graphene oxide derivatized with cyclopentylamine (GO-d-CP) as a DMSO-compatible liquid crystal alignment medium that is free from any background NMR signal for application in anisotropic NMR. This novel alignment medium facilitates optimal isotropic and anisotropic conditions within a single sample preparation, controlled by sonication, thereby enabling the measurement of anisotropic NMR parameters- residual dipolar couplings (RDC) and residual chemical shift anisotropy (RCSA). GO-d-CP offers several advantages, including ease of synthesis, isolation of solid GO-d-CP as a stable non-hygroscopic material, and maintenance of the anisotropic state stability >30 days, allowing for prolonged and repetitive experiments. Notably, post the analysis it allows for easy recovery of valuable analytes as well as GO-d-CP for reuse, enabling the routine application of anisotropic NMR in structural analysis of small molecules. We demonstrate its efficacy by analyzing the relative stereochemistry of four compounds - estrone, santonin, griseofulvin, and cinmethylin - using anisotropic NMR data.

Nonpolar graphene oxide (GO-NP): a heterogeneous liquid crystalline alignment medium for anisotropic NMR in nonpolar organic solvents - Jatheendranath, Sandesh Chickmagalur; Deshpande, Sudhindra H.; Marelli, Udaya Kiran (Materials Chemistry Frontiers, 2026)
This study reports the development of a novel nonpolar variant of graphene oxide (GO-NP) as a heterogeneous NMR alignment medium for less polar organic solvents such as CDCl3. GO-NP was obtained through a stepwise derivatisation of polar GO with C10 and C18 alkyl amines, incrementally enhancing its dispersive character. The resulting doubly functionalised GO-NP exhibits liquid crystalline properties in CDCl3, enabling anisotropic NMR characterisation of small molecules. This represents the first GO-based system effectively suitable as a heterogeneous, dispersive alignment medium for nonpolar solvents, facilitating RDC investigations with background-free NMR spectra and complete analyte recovery.